Soft Power: Political Use of A Scientific Concept - M. V. Kharkevich (Vestnik MGIMO-Universiteta)
The article discusses the use and transformation of the American scientific concept "soft power" in official Russian and US foreign policy rhetoric with the methodological help of Habermas' communicative action theory and its adoption to IR by T. Risse. In mainstream IR the proliferation of the "soft power" concept is viewed in terms of ideological competition among states. The author argues that it is better to view this process as a form of international political deliberations on new forms of power in world politics. The article shows that there's no communicative action of US and Russia based on their tentative discussion of the "soft power" concept. On of reasons might be the lack of interest of both states for the concept as an ideological basis for cooperative actions. For Russia soft power in its classical form might be used towards its near abroad and probably BIC states. In dealings with western states Russian soft power turns into lobbyism and propaganda which is strictly not soft power. US under Obama have basically refuted the concept, having changed it for analytically meaningless "smart power". The conclusion is that communicative action requires prior existence of commutative rationality. This type of rationality is evident among postmodern states - the EU member states - and apparently absent among modern states such as Russia and US.